The neuropsychological and psychosocial development of children and adolescents with lipoid proteinosis - Steenberg, Erika (University of the Free State, 2014)
Lipoid proteinosis (LiP) is a rare hereditary disease, which often results in bilateral, symmetrical and circumscribed calcifications in the mesial temporal region (especially the amygdala). While studies on the neuropsychological and neuropsychiatric difficulties of adults with LiP have been published, a lack of research focusing exclusively on the neuropsychological and psychosocial development of children and adolescents with LiP was identified. A heterogeneous group of five children and adolescents with LiP, ranging in age from 4 to 17 years, and who represented the entire known population of children and adolescents with LiP in South Africa, was assessed with standardized neuropsychological measures and behaviour checklists. Two control participants were matched to each LiP participant according to IQ, home language, right- or left-handedness, sex, race and geographic environment (urban/rural). Each child or adolescent with LiP was compared separately with the control participants matched to them, as well as with the norm groups on which the various instruments were standardized. Variable results were obtained, but in general the children and adolescents with LiP performed significantly worse (practical significance) compared with controls on measures of memory, facial emotion recognition and executive function. Three of the LiP participants also adapted less well socially than their control participants did. All the LiP participants presented with behaviour problems, although the severity and types of behaviour problems varied. Two of the participants in this study presented with amygdala lesions that may have influenced their scores on neuropsychological measures and the ratings of their behaviour, but this possibility can be substantiated only by further research that includes the imaging of controls. The study provides a baseline assessment for future longitudinal and developmental research on LiP; therefore, the study can be regarded as a pilot study.

Lipoïedproteïnose (LiP) is 'n seldsame oorerflike siekte wat dikwels tot bilaterale,simmetriese en omskrewe verkalkings in die mesal-temporale brein area (veral die amigdala) lei. Die neuropsigologiese en neuropsigiatriese probleme van volwassenes met LiP is al voorheen ondersoek, maar ̓n gebrek aan navorsing wat uitsluitlike op die neuropsigologiese en psigososiale ontwikkeling van kinders en adolessente met LiP fokus, is geïdentifiseer. ̓n Heterogene groep van vyf kinders en adolessente met LiP, wie se ouderdomme van 4 tot 17 jaar gewissel het en wat die hele bevolking van kinders en adolessente met LiP in Suid-Afrika verteenwoordig het, is met gestandaardiseerde neuropsigologiese instrumente en gedragsvraelyste geassesseer. Twee kontroledeelnemers is vir elke LiP-deelnemer volgens IK, huistaal, handvoorkeur, geslag, ras en geografiese omgewing (stad/platteland) afgepaar. Elke kind of adolessent met LiP is vergelyk met hulle spesifieke kontrole-deelnemers sowel as met die normgroep waarop die meetinstrumente gestandaardiseer is. Wisselende resultate is verkry, maar in die algemeen het die kinders en adolessente met LiP betekenisvol (praktiese beduidendheid) swakker as die kontrole-deelnemers op metings van geheue, herkenning van emosionele gesigsuitdrukking en uitvoerende funksies presteer. Drie van die LiP-deelnemers het ook sosiaal minder goed as hulle kontrole-deelnemers aangepas. Al die kinders en adolessente met LiP het gedragsprobleme getoon, alhoewel die intensiteit en tipes van gedragsprobleme gewissel het. Twee van die LiP-deelnemers het bilaterale verkalking van die amigdala getoon wat hulle resultate op neuropsigologiese instrumente en gedragsvraelyste kon beïnvloed het. Hierdie moontlikheid kan slegs bevestig word deur verdere navorsing te onderneem wat die beelding van die kontrolegroep sowel as die LiPdeelnemers insluit. Die studie verskaf 'n basislyn vir toekomstige longitudinale en ontwikkelingstudies; dus kan die studie as 'n loodsstudie gesien word.
Thesis (Ph.D (Psychology))--University of the Free State, 2014
Keywords: South Africa; Adolescent; Child; Neuropsychology; Age-related trends; Psychosocial development; Neuropsychological development; Hereditary disorder; Lipoid proteinosis; Genetic disorders in children; Pediatric neuropsychology; Lipidose -- Research; Mental retardation; Children with mental disabilities